Formulation Development of Milk Pudding Substituted with Corn Milk - เรืองธรรมสิงห์, ฤทัย; ปิยะสุวรรณยิ่ง, พรทิพย์; ศิริวงศ์, น้องนุช (KKU Science Journal, 2016)
The objective of this study was to develop pudding formula by substitution of corn milk for cow milk. The selected standard formula consisted of 36.5% milk, 14% sugar, 1.3% gelatin, 36.5% whipping cream, 11.6% egg york and 0.1% vanilla extract. The cow milk was substituted with corn milk at the level of 0 (control), 75 and 100%. The pudding formula with 100% corn milk substitution for cow milk and whipping cream (WC) was studied for comparison. The result showed that the most acceptable pudding was prepared from the formula with 100% corn milk replacement. Physical properties of the obtained pudding including L*, a*, b*, rupture strength and gel brittleness were 85.78, 4.30, 30.43, 105.47 g force and 9.94 mm, respectively. Nutritional values of the pudding with 100% corn milk could be comparable to those of the control whereas the percentage of calorie, carbohydrate and fat of the WC pudding decreased to 60.17, 36.49 and 73.80, respectively.